Project brief effects on creative thinking skills among low-ability pre-service physics teachers - Habibi Habibi; Mundilarto Mundilarto; Jumadi Jumadi; Syifaul Gummah; Sukainil Ahzan; Dwi Sabda Budi Prasetya (International Journal of Evaluation and Research in Education (IJERE), 2020)
Creative thinking is high-order thinking that is not easy to stimulate with conventional learning, especially to solve complex physics problems. However, the learning strategy chosen must be in accordance with the teaching materials and students characteristics. Creative thinking is very important especially for low-ability characteristic in solving complicated physics problems; therefore, it needs to be triggered by student-centered learning strategies such as project briefs. This research was to analyze the effect of project brief learning on creative thinking skills (CrTS) of low-ability pre-service physics theacers. Sample was selected using purposive sampling (97 people) in the initial semester pre-service physics teachers which consisted of three classes A (32 people), B (35 people), and C (30 people). Data collection through essay tests on vibration and wave material and adjusted according to the CrTS-Kim indicators. The results show that the project brief has a positive effect on creative thinking skills. The highest effect on the fluency indicator has an average of 15.7 compared to the lecture strategy, as well as the mixture with an average of 9.89, and the lowest on the originality indicator.